2017
DOI: 10.1016/j.bbmt.2016.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Integrin α4β7 in Steroid-Refractory Intestinal Graft-versus-Host Disease

Abstract: Steroid refractory acute graft-versus-host-disease of the gut is a serious complication associated with high mortality after allogeneic stem cell transplantation. Treatment options are limited and not predictably effective. We describe the treatment of steroid-refractory acute graft-versus-host-disease with vedolizumab, an antibody directed against integrin α4β7, in 6 patients. All patients responded, and 4 of 6 patients are alive with a median follow-up of 10 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 18 publications
(19 reference statements)
1
43
0
Order By: Relevance
“…Smaller case report studies of vedolizumab as second-or later-line therapy in the aGVHD setting have reported mixed results. Fløisand et al [30] reported a series of 6 patients with SR GI aGVHD, 4 of whom received vedolizumab as second-line therapy. Responses were observed in all 6 patients, and there were 4 survivors at a median follow-up of 10 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smaller case report studies of vedolizumab as second-or later-line therapy in the aGVHD setting have reported mixed results. Fløisand et al [30] reported a series of 6 patients with SR GI aGVHD, 4 of whom received vedolizumab as second-line therapy. Responses were observed in all 6 patients, and there were 4 survivors at a median follow-up of 10 months.…”
Section: Discussionmentioning
confidence: 99%
“…By inhibiting a 4 b 7 integrin, vedolizumab may interfere with gut-selective T lymphocyte trafficking, and it may be a treatment option for patients with SR GI aGVHD. This has led some clinicians to use vedolizumab off-label in these patients, and published case series have suggested clinical activity in patients with GI aGVHD [27][28][29][30]. The aims of this international, retrospective record review were to further evaluate the real-world use of vedolizumab in the off-label setting for treating patients with SR GI aGVHD, and also to assess key clinical outcomes in these patients, including those related to the safety and effectiveness of vedolizumab therapy.…”
Section: Introductionmentioning
confidence: 99%
“…For steroid-refractory patients, the overall survival at 2 years is <20% [12], and currently there are no approved second-line therapies [16]. Multiple treatments have been used off-label in this setting with rather limited success, including anti-T cell antibodies (eg, ATG, alemtuzumab), T cell-suppressive drugs (eg, mycophenolic acid, sirolimus), anticytokine biological agents (eg, TNF-a, IL-6), and a variety of others (eg, pulse cyclophosphamide, PUVA, extracorporeal photopheresis, vedolizumab, Janus-kinase inhibitors) that cause additional progressive immunosuppression, thereby significantly increasing the risk of infection and mortality [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, proof of concept studies showed that blockade of CD8 + T cell homing pathways may alleviate respective tissue damage in mouse models of aGVHD . Indeed, current phase 1 and phase 2 clinical trials with two monoclonal antibodies, vedolizumab and natalizumab, targeting ITGβ4 or ITGβ4β7, approved for the treatment of UC/CD and CD/MS, respectively, are currently exploring whether the same approach may work for the treatment of GI aGVHD in humans, as well . Although less well documented, there is some evidence that the homing preferences of activated CD4 + Th and Treg cells are also altered in aGvHD.…”
Section: Introductionmentioning
confidence: 99%